-4(k-7)=

Simple and best practice solution for -4(k-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(k-7)= equation:


Simplifying
-4(k + -7) = 0

Reorder the terms:
-4(-7 + k) = 0
(-7 * -4 + k * -4) = 0
(28 + -4k) = 0

Solving
28 + -4k = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-28' to each side of the equation.
28 + -28 + -4k = 0 + -28

Combine like terms: 28 + -28 = 0
0 + -4k = 0 + -28
-4k = 0 + -28

Combine like terms: 0 + -28 = -28
-4k = -28

Divide each side by '-4'.
k = 7

Simplifying
k = 7

See similar equations:

| 2*8=x | | 3(2c-5)= | | x+x-2=68 | | -6t-7=10 | | 8(v+1)-4v=2(2v+4)-13 | | (4/7)(5/8) | | y-3=2x+y-11 | | -.10(7)+.20x=.05(x-2) | | 9(n-1)=-18 | | (t-5)(t-5)=2(5-t) | | (3y-8)=180 | | 4x+6+13=17 | | 650s=235000-350d | | 2x+-4x=-2 | | 1ot-11=11t-2 | | 5m+4=-1 | | 6x-1=4x-73 | | 2x+10+90+3x=180 | | sin4x=-2/5 | | (y^2)-10y+4x+53=0 | | 6x=4x+9 | | X^2+6x+17x=0 | | 7x-13=6x+2 | | 2-1.5x=4-1.5x | | (3z+1)(4z+3)=0 | | 4x+21+2x+9=90 | | ((-2x^3)(y^-4)/(3x^-1)(y^4))^-3 | | Log(5-x)=12 | | 9*10^4*2.4*10^-5/2*10^-1*6*10^3 | | X^2+8x-6.5=0 | | 2x^2+3x+7=y | | 3x+27+2x+43=180 |

Equations solver categories